Performance improvement of three-level neutral-point-clamped electric-starter-generator system for more electric aircraft - Guo, Feng (2021)
The more-electric-aircraft concept is receiving more and more attention in the development of next-generation large, commercial aircraft due to its high reliability, low maintenance costs and good environmental impact. To satisfy these expectations, aerospace systems are undergoing a transition from pneumatic, hydraulic and mechanical power to electrical counterparts. With the help of cutting-edge active rectification technology, a cutting-edge aircraft electric starter-generator system tends to substitute the typical three-stage wound-field synchronous generator for avoiding mechanical failures, especially for high-speed operation. Since the three level neutral-point-clamped (3L-NPC) converter plays an essential role in the energy conversion path, this thesis primarily focuses on the following advanced pulse-width modulation (PWM) strategies that aim to enhance the reliability and efficiency of the entire system without any additional hardware.